Estudo da aplicação de filmes automontados de PAH/PEDOT: PSS em membranas de Nafion® - Almeida, Tiago Pedroso de (2013)
The present work aimed the fabrication of layer-by-layer nanostructured films of poly (allylaminehydrochloride) (PAH) and poly(3,4-ethylenedioxythiophene) poly(styrenesulfonate) (PEDOT:PSS) onto Nafion® 212 membranes. Nafion® is the most used polyelectrolyte in proton exchange membranes (PEM) fuel cells due to its high proton conduction and good chemical stability at ambient temperature. Therefore, this polyelectrolyte presents some disadvantages due to the high methanol permeability when applied in Direct Methanol Fuel Cells (DMFC), reducing drastically the performance of the device. We studied how ultrathin films of PAH/PEDOT:PSS influence the methanol permeability and proton conduction in the LbL modified membranes. Results indicated good adherence of the LbL films onto Nafion® 212 and also good action as a methanol barrier. Nonetheless, together with the methanol blocking there was also a reduction in the proton conductivity, which occurs due to the LbL dipping deposition on both sides of Nafion® 212, trapping water inside the Nafion membrane, and certainly affecting the proton conduction. Moreover, the LbL film deposition might use some important chemical groups present at the Nafion® surface, used to water permeation, also affecting the proton permeation throughout the membrane.